Reconstructing the Concept of Marriage Guardianship - Nur, Iffatin; Ridho, Moh. Lutfi; Akhyak, Akhyak (Human Sustainability Procedia, 2024)
This study aims to reveal the obsolescence of Islamic law concerning the concept of guardianship of children that so far still seems patriarchal. In this context, there is a phenomenon against justice and benefits for children. In a certain position, a child who should have his/her rights in the form of protection, financing, and education is simply abandoned, encouraging someone to adopt him/her and fulfill the obligations that should be imposed on the child’s biological parents. This condition raises a polemic when a female child has grown up and is about to get married, regarding “Who has the right to be the guardian in her marriage?” and “What exactly is the essence of guardianship?” This qualitative study employed a multi-system study model on the perceptions and views of the Indonesian Islamic Marriage Registrars Association (Asosiasi Penghulu Republik Indonesia or APRI, Ind.)  and the Indonesian Family Law Lecturers Association (Asosiasi Dosen Hukum Keluarga Islam or ADHKI, Ind.) to reveal the methodological and practice aspects of guardianship in Indonesia. The results show that the reconstruction of the concept of guardianship of adopted children in the perspective of APRI and ADHKI based on fiqh (Islamic jurisprudence) of reciprocity resulted in a model of reciprocal rights and obligations between children and parents as well as husband and wife that provides opportunities for a mother who has taken care of her daughter and an adoptive father who has raised a female child to become a marriage guardian.